A 16 year study of injuries to professional boxers in the state of Victoria, Australia. Issue 4 (31st July 2003) - Zazryn, T R; Finch, C F; McCrory, P
Abstract : Objectives: Concerns about the significant injury risks in boxers have been well documented. To inform the continuing debate, updated information about the risk of injury for participants, and suitable means of modifying or preventing these risks, need to be identified. Methods: Data describing all professional boxing fight outcomes and injuries sustained during competition, from August 1985 to August 2001, were obtained from the Victorian Professional Boxing and Combat Sports Board. Results: A total of 107 injuries were recorded from 427 fight participations, corresponding to an injury rate of 250.6 injuries per 1000 fight participations. The most commonly injured body region was the head/neck/face (89.8%), followed by the upper extremities (7.4%). Specifically, injuries to the eye region (45.8%) and concussion (15.9%) were the most common. About three quarters of all injuries were lacerations/open wounds or superficial. No information was available on the mechanism of injury. Conclusions: Future research should collect information on the mechanism of injury, as this is crucial for the development and implementation of effective injury prevention strategies. A suggested boxing injury report form is provided to facilitate this.